An Ultra-Stable, High-Energy and Wide-Temperature-Range Aqueous Alkaline Sodium-Ion Battery with the Microporous C4N/rGO Anode - Li, Mengxiao; Li, Rui; Ma, Huige; Yang, Mingsheng; Dai, Yujie; Yu, HaiPing; Hao, Yuxin; Wang, Zhihui; Wang, Bei; Hu, Mingjun; Yang, Jun (Nano-Micro Letters, 2025)
Common anode materials in aqueous alkaline electrolytes, such as cadmium, metal hydrides and zinc, usually suffer from remarkable biotoxicity, high cost, and serious side reactions. To overcome these problems, we develop a conjugated porous polymer (CPP) in-situ grown on reduced graphene oxide (rGO) and Ketjen black (KB), noted as C4N/rGO and C4N/KB respectively, as the alternative anodes. The results show that C4N/rGO electrode delivers a low redox potential (−0.905 V vs. Ag/AgCl), high specific capacity (268.8 mAh g−1 at 0.2 A g−1), ultra-stable and fast sodium ion storage behavior (216 mAh g−1 at 20 A g−1) in 2 M NaOH electrolyte. The assembled C4N/rGO//Ni(OH)2 full battery can cycle stably more than 38,000 cycles. Furthermore, by adding a small amount of antifreeze additive dimethyl sulfoxide (DMSO) to adjust the hydrogen bonding network, the low-temperature performance of the electrolyte (0.1 DMSO/2 M NaOH) is significantly improved while hydrogen evolution is inhibited. Consequently, the C4N/rGO//Ni(OH)2 full cell exhibits an energy density of 147.3 Wh Kg−1 and ultra-high cycling stability over a wide temperature range from −70 to 45 °C. This work provides an ultra-stable high-capacity CPP-based anode and antifreeze electrolyte for aqueous alkaline batteries and will facilitate their practical applications under extreme conditions. Highlights: 1 An integrated conjugated microporous polymer composite electrode (C4N/rGO) with high conductivity, large specific surface area and good solvent resistance was prepared by in-situ growth. 2 An antifreeze alkaline electrolyte (0.1 DMSO/2 M NaOH) was developed to broaden the operation temperature zone and voltage window of the aqueous alkaline battery. 3 The prepared aqueous alkaline battery exhibits a high energy density (147.3 Wh Kg−1 at 25 °C), outstanding long cycling stability and excellent wide-temperature-range performance (−70 to 45 °C).